Analisis Kemampuan Komunikasi Matematis Materi Operasi Hitung Perkalian dan Pembagian Siswa SDN 2 Karangmulyo - Amalinda Enggarwanti; Kartinah Kartinah; Sukamto Sukamto (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
Mathematical communication ability is an ability that must be possessed by students in mathematics because mathematics is a communication tool that is closely related to everyday life. This study aims to analyze the mathematical communication skills of students, especially the material for multiplication and division arithmetic operations. This study uses a descriptive qualitative approach by collecting data through tests, interviews, and documentation. The results of the analysis show that students at have a moderate level of mathematical communication, this is in accordance with the 6 subjects who get the same category. The level of mathematical communication that is classified as moderate has communication that almost fulfills most of the indicators of mathematical communication, most of them write down the answers, it's just that the answers are incomplete, the answers from the 6 subjects do not write conclusions at all, besides that students are not careful and thorough in work on the problem so that it affects the results of the value obtained.